Upaya Meningkatkan Hasil Belajar Kenampakan Alam dan Sosial Negara Asia Tenggara Melalui Penerapan Model Team Group Tournament Siswa Kelas VI UPTD SD N 06 Sariak Laweh Kecamatan Akabiluru Tahun Pelajaran 2021/ 2022 - Indra Yanti (Departement of Mathematics Education, 2022)
This study aims to find out: Is cooperative learning the Team Group Tournament model able to improve social studies learning outcomes on natural and social features in Southeast Asia in class VI UPTD SD Negeri 06 Sariak Laweh, Akabiluru District, Lima Puluh Kota Regency in the 2021/2022 academic year. The research method used is classroom action research (CAR) which consists of 2 cycles. The subjects of the study were students of class VI UPTD SD Negeri 06 Sariak Laweh, Akabiluru District, Fifty Cities District, in the 2021/2022 academic year as many as 7 students. Data analysis used comparative descriptive analysis techniques by comparing the initial conditions with the results achieved in each cycle, and qualitative descriptive analysis of observations by comparing the results of observations and reflections in cycle I and cycle II. With the application of cooperative learning learning model Team Group Tournament (TGT) on natural and social features in Southeast Asia in class VI UPTD SD Negeri 06 Sariak Laweh, Akabiluru District, Fifty Cities Regency, for the 2021/2022 academic year. At the end of the second cycle, it is known that there has been an increase in the class average of 31.47%, from the average initial condition test of 59.24 to 90.71. Meanwhile, student learning completeness has increased by 42.85%, from the initial conditions that were already completed only 3 students to 6 students. Thus, most of the sixth grade students of UPTD SD Negeri 06 Sariak Laweh experienced an increase in learning outcomes on natural and social features in Southeast Asia.